Growth Hormone Increases BDNF and mTOR Expression in Specific Brain Regions after Photothrombotic Stroke in Mice - Sonia Sanchez-Bezanilla; Daniel J. Beard; Rebecca J. Hood; N. David Åberg; Patricia Crock; Frederick R. Walker; Michael Nilsson; Jörgen Isgaard; Lin Kooi Ong (Neural Plasticity)
Aims. We have shown that growth hormone (GH) treatment poststroke increases neuroplasticity in peri-infarct areas and the hippocampus, improving motor and cognitive outcomes. We aimed to explore the mechanisms of GH treatment by investigating how GH modulates pathways known to induce neuroplasticity, focusing on association between brain-derived neurotrophic factor (BDNF) and mammalian target of rapamycin (mTOR) in the peri-infarct area, hippocampus, and thalamus. Methods. Recombinant human growth hormone (r-hGH) or saline was delivered (0.25 μl/hr, 0.04 mg/day) to mice for 28 days, commencing 48 hours after photothrombotic stroke. Protein levels of pro-BDNF, total-mTOR, phosphorylated-mTOR, total-p70S6K, and phosporylated-p70S6K within the peri-infarct area, hippocampus, and thalamus were evaluated by western blotting at 30 days poststroke. Results. r-hGH treatment significantly increased pro-BDNF in peri-infarct area, hippocampus, and thalamus (p<0.01). r-hGH treatment significantly increased expression levels of total-mTOR in the peri-infarct area and thalamus (p<0.05). r-hGH treatment significantly increased expression of total-p70S6K in the hippocampus (p<0.05). Conclusion. r-hGH increases pro-BDNF within the peri-infarct area and regions that are known to experience secondary neurodegeneration after stroke. Upregulation of total-mTOR protein expression in the peri-infarct and thalamus suggests that this might be a pathway that is involved in the neurorestorative effects previously reported in these animals and warrants further investigation. These findings suggest region-specific mechanisms of action of GH treatment and provide further understanding for how GH treatment promotes neurorestorative effects after stroke.